A plastid DNA phylogeny of tribe Miliuseae: Insights into relationships and character evolution in one of the most recalcitrant major clades of Annonaceae1. Issue 4 (1st April 2014) - Chaowasku, Tanawat; Thomas, Daniel C.; van der Ham, Raymond W. J. M.; Smets, Erik F.; Mols, Johan B.; Chatrou, Lars W.
Abstract : Premise of the study: Tribe Miliuseae (∼25 genera and ∼510 species) includes a substantial part of the species and generic diversity in the pantropical flowering‐plant family Annonaceae (∼108 genera and ∼2400 species). Previous molecular phylogenetic analyses have failed to resolve the backbone phylogeny of the tribe, impeding biogeographical and evolutionary studies. We use a dense generic taxon sample (∼89% of generic diversity in Miliuseae) and plastid DNA sequence data (∼7 kb) to clarify the phylogenetic relationships of and within the tribe. Methods: Parsimony and Bayesian phylogenetic reconstructions and ancestral character‐state reconstructions of several reproductive characters were performed. Key results: Dendrokingstoniae, Monocarpieae, and Miliuseae are recovered in a strongly supported clade, and each tribe is strongly supported as monophyletic. Miliuseae are characterized by a synapomorphic cryptoaperturate/disulculate pollen apertural system. Stenanona is shown to be nested within the paraphyletic genus Desmopsis . The only Neotropical clade ( Sapranthus, Tridimeris, Desmopsis, and Stenanona ) in the predominantly Asian Miliuseae is shown to be closely related to an undescribed genus from continental Southeast Asia and the Indo‐Malayan and Austral‐Pacific genus Meiogyne . Ancestral character‐state reconstructions of several reproductive characters that are diagnostically important at the generic level indicate a considerable degree of homoplasy. Conclusions: The results improve our understanding of the relationships of and within Miliuseae, but parts of the backbone of the phylogeny remain poorly supported. Additional data from variable nuclear markers or reduced‐genome‐representation approaches seem to be required to further resolve relationships within this recalcitrant clade.